Rural microfinance and microenterprise: informal revolution / edited by Amitabh Bharatnagar - "Bhatnagar, Amitabh (ed.)" (New Delhi, 2008)
This book attempts an overview of varied dimensions, constraints and best practices related to Rural Microfinance and Microenterprise, alongwith indepth papers on some key/emerging focus areas by erudite development practitioners scholars. The book strives to work out the modalities of a flexible multipronged strategy for discovering the pathway towards 'formalization' of Informal Sector finance and enterprise in the difficult rural domain of the developing world, amidst heterogeneity of options. This is a pioneering venture in considering microfinance and microenterprise as a continuum with integral and logical linkages. This high quality knowledge management Ready Referencer will be useful to all stakeholders actors in the development arena-policy makers, microfinance, microenterprise field professionals, grassroots workers, activists, scholars and researchers of various institutions involved in Rural Management and Development.
Keywords: Microfinance-India